Employer Branding and Digital Recruitment: Their Impact on Job Seekers’ Interest at Bukit Raya Sekawan Mining Company - Yudhistira Anugerah Pratama; Louisiani Mansoni Isnajati; Husnawati Djabbar; Gina Nastia; Iqbal Syaefulloh (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study investigates the influence of employer branding and digital recruitment on job seekers’ interest at Bukit Raya Sekawan Mining Company. With increasing competition in the labor market and the evolving expectations of modern job seekers, organizations must strategically adapt their talent acquisition methods. A quantitative approach was employed using a structured questionnaire distributed to 61 participants. The findings revealed that both employer branding and digital recruitment significantly and positively impact job seekers' interest. Employer branding was found to have a stronger effect, highlighting the importance of clear and authentic communication of organizational values. Digital recruitment also plays a critical role in reaching and engaging candidates through interactive platforms. Together, these strategies form a synergistic approach to enhancing organizational attractiveness and applicant engagement. The results underscore the need for continuous refinement of recruitment practices to ensure consistency between external branding and internal realities, thus improving job-person fit and sustaining applicant interest.